(untitled) (Journal of Oriental Studies, 2021)
The article considers data about the life of one of the first Sufis – Ibrahim ibn Adham, known for holiness in the Muslim world. The author set the goal – to study the life of Saint on the basis of source data. Biographical data is rather scarce. In Arabic-language sources there is data on the date of Saint death. The main source is oral narratives, which are used by aqyns, storytellers. Verbal texts among the people served as an excellent source in the creation of qissa. In the Turkic world, there was an idea of the worthiness of creating works on Shaykh Saints. In turn, the belief contributed to the emergence of many versions of “Qissa-i Ibrahim ibn Adham”. The value of the studying source lies in the fact that they raise moral and ethical standards that guided the Shaikh Saints in their activities. In the process of work, Kazakh, Uyghur and Turkish versions of the narrative and translations of hagiographic works into Turks were revealed, which indicates the wide distribution of such works. Interest in such texts remained until the 20th century. The rare collections of libraries in Almaty contain lithographic editions of the studied source. The sources identified in the process of work were studied in a comparative aspect, the works of well-known orientalists on Sufism were involved. The study contributes to the expansion of the source base on Sufism, the results achieved can be used not only by specialists of orientalists, but also by University teachers. Keywords: Islam, manuscript, life of a Sufi, translations of treatises, Central Asia.